Identification, Quantification, and System Analysis of Protein N‐ε Lysine Methylation in Anucleate Blood Platelets. Issue 11 (9th May 2019) - Rocheleau, Anne D.; Melrose, Alexander R.; Cunliffe, Jennifer M.; Klimek, John; Babur, Özgün; Tassi Yunga, Samuel; Ngo, Anh T. P.; Pang, Jiaqing; David, Larry L.; McCarty, Owen J. T.; Aslan, Joseph E.
Abstract: Protein posttranslational modifications critically regulate a range of physiological and disease processes. In addition to tyrosine, serine, and threonine phosphorylation, reversible N‐ε acylation and alkylation of protein lysine residues also modulate diverse aspects of cellular function. Studies of lysine acyl and alkyl modifications have focused on nuclear proteins in epigenetic regulation; however, lysine modifications are also prevalent on cytosolic proteins to serve increasingly apparent, although less understood roles in cell regulation. Here, the methyl‐lysine (meK) proteome of anucleate blood platelets is characterized. With high‐resolution, multiplex MS methods, 190 mono‐, di‐, and tri‐meK modifications are identified on 150 different platelet proteins—including 28 meK modifications quantified by tandem mass tag (TMT) labeling. In addition to identifying meK modifications on calmodulin (CaM), GRP78 (HSPA5, BiP), and EF1A1 that have been previously characterized in other cell types, more novel modifications are also uncovered on cofilin, drebin‐like protein (DBNL, Hip‐55), DOCK8, TRIM25, and numerous other cytoplasmic proteins. Together, the results and analyses support roles for lysine methylation in mediating cytoskeletal, translational, secretory, and other cellular processes. MS data for this study have been deposited into the ProteomeXchange Consortium via the PRIDE partner repository with the dataset identifier PXD012217.